Mediatization and Sport: A Bottom-Up Perspective. (October 2018) - Skey, Michael; Stone, Chris; Jenzen, Olu; Mangan, Anita
The concept of mediatization has proved remarkably popular in the past decade, although recent critiques have challenged its media-centrism, ahistoricism, and conceptual clarity. In this article, we draw on the work of those who suggest that mediatization is best deployed as a means of understanding particular social domains and the ways in which institutions and actors orientate their activities towards media. Using association football, or soccer, as our focus we offer a bottom-up perspective using data gathered from research workshops with young people in England. These not only demonstrate the extent to which football is followed through a range of media platforms but also how broader understandings of the game are shaped by these engagements. Moreover, we adapt insights from recent phenomenological approaches to media to focus on the practical, embodied forms of knowledge and habit that shape how football is currently played, followed, and debated.